Particle Breakage Mechanisms in a Horizontal Stirred Mill: A Morphological Study - Roufail, Reem; Klein , Bern (Technological Innovation in Engineering Research Vol. 1, 2022)
In this study, particles are ground in a stirred mill and their morphological features were analyzed using automated and manual detection methods. The morphological surface properties of product particles are determined by particle breakage mechanisms such as fracture or abrasion. Promoting breakage mechanism that would achieve mineral liberation at the lowest energy consumption is imperative to conserve comminution energy consumption. Particles that break along grain boundaries (intergranular) are expected to have rough surfaces, whereas particles that break across grain boundaries (transgranular) are expected to have smoother surfaces.According to the literature and popular assumption, high-speed stirred mills break particles through attrition. Along with attrition, fracture was found to be an essential breakage mechanism in this study. The input stress level, in the form of mill agitator speed, and the type of mineral are both factors in the breakage mechanism. Galena fractures along the grain boundaries at higher agitator speeds, whereas quartz abrades across the grain boundaries.